Makna Simbolis Bahasa Kiasan dalam Antologi Puisi “Selamat Menunaikan Ibadah Puisi” Karya Joko Pinurbo - Eka Yoga Pranata; Irma Arifah; Widi Suharto (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This study discusses the symbolic meaning contained in the use of figurative language in the poetry anthology Selamat Menunaikan Ibadah Puisi by Joko Pinurbo. This study uses a qualitative descriptive approach with a semiotic analysis method as a theoretical basis, which allows researchers to interpret the signs and symbols in the poetic texts in depth. The results of the study show that the figurative language in the poems does not only function as rhetorical decoration or mere linguistic ornamentation, but has a strong and essential symbolic function in conveying hidden messages and the poet's inner emotions. Symbols such as "storm", "refrigerator", "twilight", "window", "door", "river", and others are not only concrete images, but convey deep meanings related to inner suffering, past memories, the search for self-identity, feelings of alienation, and the search for the universal meaning of life. In addition, this study also identifies various types of figurative language used by Joko Pinurbo in the anthology, including metaphor, simile, personification, hyperbole, synecdoche, paradox, and irony. All types of figurative language are skillfully used to enrich the meaning of poetry and deepen the aesthetic experience of readers, allowing them to feel and reproduce the messages hidden behind the words. Thus, this study confirms that the use of figurative language in poetry is not only a literary technique, but also a powerful medium of expression and a means of communicating complex meanings in modern literary works. This study discusses the symbolic meaning contained in the use of figurative language in the poetry anthology Selamat Menunaikan Ibadah Puisi by Joko Pinurbo. This study uses a qualitative descriptive approach with a semiotic analysis method as a theoretical basis, which allows researchers to interpret the signs and symbols in the poetic text in depth.